2019
DOI: 10.1093/fampra/cmz010
|View full text |Cite
|
Sign up to set email alerts
|

Practical mixed methods strategies used to integrate qualitative and quantitative methods in community-based primary health care research

Abstract: Background Mixed methods (MM) are common in community-based primary health care (CBPHC) research studies. Several strategies have been proposed to integrate qualitative and quantitative components in MM, but they are seldom well conceptualized and described. The purpose of the present review was to identify and describe practical MM strategies and combinations of strategies used to integrate qualitative and quantitative methods in CBPHC research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
2
27
0
4
Order By: Relevance
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
See 3 more Smart Citations
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
“…A key finding of this review is that the reporting of the mixed methods articles published in the eight journals examined showed a need for improvement. In line with previous reviews [8,35], none of the articles included in our review fulfilled all six GRAMMS criteria and none of the six criteria was fulfilled by all the articles. The reporting quality was not consistent across the six criteria, with variations according to the particular mixed methods feature being examined.…”
Section: Main Findingssupporting
confidence: 68%
See 2 more Smart Citations
“…A cross-sectional mixed-methods study 17 , 18 was chosen for the quantitative component of this research. We assessed factors such as personal information, experience, knowledge, attitude and practices regarding DPC among nurses in PCUs.…”
Section: Methodsmentioning
confidence: 99%